Single nucleotide polymorphism of leptin and leptin receptor genes in oral cancer - a systematic review - Hasanbasri, Siti Hana Ilyana; Amir Sabri, Nur Armidha Nadihah; Mokhtar@Makhtar, Khairani Idah; Mustafa Al-Ahmad, Basma Ezzat; Mohd Ibrahim, Mohamad Shafiq; Subramaniam, Pram Kumar (IIUM Press, 2024)
Oral cancer is one of the serious health problems diagnosed worldwide including Malaysia. While much research has been done on the gene polymorphism of leptin and leptin receptor genes in other cancers, few researchers have considered oral cancer. Hence, this study aims to provide an insight into the association of a single nucleotide polymorphism of leptin and leptin receptor genes with oral cancer, as well as its contribution in increasing the risk for oral cancer development. Literature searches were conducted in six databases including Scopus, ScienceDirect, Web of Science, PubMed, Google Scholar, and Dimensions; focusing on articles published between 2000 to 2020. All relevant articles were screened accordingly using search terms “leptin”, “leptin receptor”, “single nucleotide polymorphism” and “oral cancer”. A total of 2699 articles were retrieved. After following the inclusion and exclusion criteria, only four articles were included in this systematic review highlighting the three commonly studied polymorphic variant of leptin and leptin receptor which are LEP -2548 G/A, LEPR Gln223Arg, and LEPR K109R. Single nucleotide polymorphism of leptin and leptin receptor genes specifically LEPR Gln223Arg and LEP -2548 G/A may increase the risk of development of oral cancer. There were limited sources available to support the findings. Further research and investigations are needed to explore the mechanism of leptin and leptin receptor genes in the development of oral cancer.